The tactics of managing children and adolescents when twisting the uterine appendages from the position of international standards - Zalina K. Batyrova; Zaira K. Kumykova; Elena V. Uvarova; Vladimir D. Chuprynin; Natalya A. Buralkina; Irina A. Kiseleva; Fatima Sh. Mamedova; Madina A. Chundokova (IP Berlin A.V., 2020)
Background. Adnexal torsion (AT) takes fifth place among all emergency gynecological conditions. Suspicion of AT requires immediate diagnosis and urgent surgical treatment. The most common causes of AT are various volumetric formations, such as functional or dermoid ovarian cysts, contributing to an increase in its volume and/or anomalies in the development of the ligamentous apparatus. Timely diagnosis and detorsion contributes to the full restoration of impaired venous outflow and lymphatic drainage of the ovarian tissue, preventing the development of severe ischemia and necrosis. Over the past few decades, a surgical organ-preserving approach in managing patients with AT has been the gold standard of care. Materials and methods. The article describes the results of a retrospective study of cases of AT in children and adolescents treated at the Department of Pediatric and adolescent gynecology Kulakov National Medical Research Center for Obstetrics, Gynecology and Perinatology with an assessment of the clinical and anamnestic features of this cohort of patients and the choice of therapeutic tactics. Conclusion. A multidisciplinary approach is critical to optimizing the delivery of care in cases of AT, including minimally invasive detorsion and preserving the functionality of the ovary as a treatment standard that should be used in the management of children and adolescents.